2018
DOI: 10.1371/journal.pone.0206607
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven, voxel-based analysis of brain PET images: Application of PCA and LASSO methods to visualize and quantify patterns of neurodegeneration

Abstract: Spatial patterns of radiotracer binding in positron emission tomography (PET) images may convey information related to the disease topology. However, this information is not captured by the standard PET image analysis that quantifies the mean radiotracer uptake within a region of interest (ROI). On the other hand, spatial analyses that use more advanced radiomic features may be difficult to interpret. Here we propose an alternative data-driven, voxel-based approach to spatial pattern analysis in brain PET, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…It seeks two mixing matrices (W 1 and W 2 ) such that each pair of canonical variates U i and V i ( i = 1…5) has maximum correlation across the two datasets, while the canonical variates within each dataset are orthogonal (U i and U j are uncorrelated)For i = 1…5,maxW1i,W2iitaliccorr(),Xnormalwitalichiten×W1iYwhiten×W2iUi=Xwhiten×W1i;Vi=Ywhiten×W2iThus, the transformed data (canonical variates U and V) contain common (maximally correlated between two datasets) subject profiles, which are composed of subject score of each subject (representing the subject weights for the corresponding mixing matrix). Subject scores are in Z -score form with a mean of zero and a standard deviation of one.Least absolute shrinkage and selection operator (LASSO) (Klyuzhin et al, 2018a; Tibshirani, 2011) is then applied to regress the canonical variates (U i and V i ) from the original datasets X and Y to compute regression coefficients (CCA weights A and B) and regression residuals (X residual and Y residual ) as shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seeks two mixing matrices (W 1 and W 2 ) such that each pair of canonical variates U i and V i ( i = 1…5) has maximum correlation across the two datasets, while the canonical variates within each dataset are orthogonal (U i and U j are uncorrelated)For i = 1…5,maxW1i,W2iitaliccorr(),Xnormalwitalichiten×W1iYwhiten×W2iUi=Xwhiten×W1i;Vi=Ywhiten×W2iThus, the transformed data (canonical variates U and V) contain common (maximally correlated between two datasets) subject profiles, which are composed of subject score of each subject (representing the subject weights for the corresponding mixing matrix). Subject scores are in Z -score form with a mean of zero and a standard deviation of one.Least absolute shrinkage and selection operator (LASSO) (Klyuzhin et al, 2018a; Tibshirani, 2011) is then applied to regress the canonical variates (U i and V i ) from the original datasets X and Y to compute regression coefficients (CCA weights A and B) and regression residuals (X residual and Y residual ) as shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
“…Least absolute shrinkage and selection operator (LASSO) (Klyuzhin et al, 2018a; Tibshirani, 2011) is then applied to regress the canonical variates (U i and V i ) from the original datasets X and Y to compute regression coefficients (CCA weights A and B) and regression residuals (X residual and Y residual ) as shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
“…PCA converts a set of correlated variables into a smaller number of uncorrelated new variables, where the new sample includes the most information from the original data [ 2 , 23 , 24 ]. Let X ∈ R n × m be the original data matrix with n samples and m variables, which can be explained as: …”
Section: Background Of Pcamentioning
confidence: 99%
“…Previous studies have shown that the metabolic patterns of Parkinson's disease (PD) and atypical Parkinson's syndrome, e.g., multiple system atrophy (MSA), progressive supranuclear palsy (PSP), and corticobasal degeneration (CBD), were different [11]. However, it is usually difficult to quantitatively analyze abnormalities in different brain regions accurately [12]. Because of PET's relatively low spatial resolution and the complexities of brain anatomy, the analysis of regional PET quantification relies on MRI.…”
Section: Introductionmentioning
confidence: 99%